2003
DOI: 10.1046/j.1442-8903.4.s.3.x
|View full text |Cite
|
Sign up to set email alerts
|

Using soil and litter arthropods to assess the state of rainforest restoration

Abstract: Summary The present study investigated recolonization patterns of selected soil and litter arthropods following replanting of pasture with rainforest species in the Mary River catchment of eastern subtropical Australia. While extensive research has been conducted in rehabilitated mined sites in Australian dry sclerophyll forests, very little attention has been paid to rainforest restoration on previously pastoral land. We examined the utility of soil and litter arthropod groups for monitoring the progress of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 25 publications
4
74
0
10
Order By: Relevance
“…Se de um lado uma serapilheira mais profunda representa maior oferta de alimento e locais para nidifi cação, por outro, ela proporciona um microclima favorável à vida de um número maior de espécies (Nakamura et al 2003).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se de um lado uma serapilheira mais profunda representa maior oferta de alimento e locais para nidifi cação, por outro, ela proporciona um microclima favorável à vida de um número maior de espécies (Nakamura et al 2003).…”
Section: Discussionunclassified
“…Lassau & Hochuli (2004) encontraram correlação negativa entre a riqueza de formigas e a complexidade do ambiente em fl orestas da Austrália. Nakamura et al (2003) demonstraram que, entre um grande conjunto de variáveis ambientais, a profundidade da serapilheira foi a que mais infl uenciou a riqueza de formigas em experimentos de restauração fl orestal.…”
unclassified
“…For such groups, more intensive sampling typically never generates curves that completely fl atten out and reach a plateau (Fisher 1999). Furthermore, several important epigeic taxa such as ants and termites have patchy distribution (Soares & Schoereder 2001, Nakamura et al 2003, 2007, which results in new species being found sporadically.…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial invertebrates are also extremely abundant: estimates in the Brazilian Amazon suggest that over one billion invertebrates, most of which are edaphic arthropods, are present in one hectare of forest (WIL-SON 1987). Invertebrates have been used to assess restoration success at mines (ANDERSEN 1993, SIMMONDS et al 1994, riparian woodland (WILLIAMS 1993), rainforests (NAKAMURA et al 2003), and temperate forests (WILLETT 2001). In their review of the ecosystem services that are affected by invertebrate activities, LAVELLE et al (2006) highlight the contribution of the soil biota to water supply, nutrient cycling, soil formation, primary production, flood and erosion control, and climate regulation.…”
mentioning
confidence: 99%